Sandwich-like CNTs@SnO2/SnO/Sn anodes on three-dimensional Ni foam substrate for lithium ion batteries - Zhang, J.; Ma, Z.; Jiang, W.; Zou, Y.; Wang, Y.; Lu, Chunsheng (Elsevier, 2016)
Lithium ion battery anodes derived from Sn and Sn oxides have been of considerable interest because they can store twice lithium ions more than the graphite. However, large volume change occurs when lithium ions are inserted and extracted from these active materials, which causes internal damage to electrode and results in the loss of capacity and recharge ability. Here, we prepared sandwich-like CNTs@SnO2/SnO/Sn anodes by using composite electrodeposition and anodic oxidation on three-dimensional (3D) Ni foam. It is shown that the phases of C, Sn2 +, Sn4 + and Sn are the sandwich-like structure in CNTs@SnO2/SnO/Sn anode. Such a 3D anode can provide more superior electrochemical, mechanical properties and extra space to get good cycle performance with the first discharge capacity of 1260 mA h g− 1 and 99% coulombic efficiency.